ANALISIS KOREOGRAFI TARI INDANG TAPUAK SITUJUAH PADA SANGGAR SENTAK SAIRIANG DI KOTA PARIAMAN - Fernanda Putri; Nerosti Nerosti; Herlinda Mansyur (FBS Universitas Negeri Padang, 2018)
Abstract This article aims to disclose and describe analysis Dance choreography Indang Tapuak Situjuah on Sentak Sairiang Studio. This type of qualitative research is using descriptive motode. The object of this research is to analyze the Dance choreography Indang Tapuak situjuah on Sentak Sairiang in the workshop of Pariaman. The type of data in this study is the primary data and secondary data. The technique of collecting data in this research is the observation, interviews, and documentation. The results showed that the shape of the choreography Dance Indang Tapuak Situjauh using the composition of large groups. In Indang Tapuak Situjuah Dance menggamabrkan quiet, cheerful atmosphere and excitement, Indang Tapuak Situjuah motion consists of 42 motif motion performed by dancers Indang Tapuak Situjuah with Frisky when the dancers play rapa'i the floor patterns and varied as there is in the form of a diagonal straight line, circle, rectangle, triangle, sometimes dancers spread dipentas three people form a triangle on the back in the middle of performances and four dancers line up abreast at the front. So the interaction between dancer and spectator. Contents of the Tapuak Dance in Indang Situjuah, reflects the idea or notion of Indang Tigo Jerong Dance which has three motif motion and choreographers develop it. The lines were crossed by the dancers to form as many as 10 group formation design. Tari Indang Tapuak Situjuah also has 10 top design that is focused upon the design, low, flat, angle, and high contrast. Dance costumes in Indang Tapuak Situjuah is the costume tradition has been dikreasikan in Pariaman, which had dikreasikan in accordance with the needs of Indang Tapauak Situjuah Dance with does not eliminate the costumes typical of the mngambarkan a girl minang. Music and Dance Tapuak Situjuah has the content, instruments played fast tempo, slow and fast, which can convey the mood and expression of Indang Tapuak Dance Situjuah. the instruments used Talempong, Gandang, shehnai and jimbe. Pawpaw and jimbe instrument is very instrumental in menbangkitkan atmosphere in Indang Dance Tapuak Situjuah, with a flow of calm, joyful and settlement. Key words: analysis of Dance choreography, Indang Tapuak Situjuah